Evaluation of anticancer properties of carica papaya male flower on breast cancer - Rohana, Jamaludin (2025)
Medicinal herbs were historically utilized for various healing effects by ancient civilizations. At present, the recognition of utilizing plants specifically for anticancer effects has remained on the rise. Various tests were conducted to identify the phytochemicals present in the medicinal plants that linked to therapeutic effects, such as anticancer activities. Carica papaya, a plant from the Caricaceae family is widely grown in tropical nations. Its flowers are traditionally consumed as vegetables to enhance societal diets and promote individual growth. Nonetheless, the anticancer potential of C. papaya flowers, particularly against breast cancer, remains underexplored. This research aimed to explore the anti-proliferative effects of extract from C. papaya flower on the MCF-7 human breast cancer cell line. Soxhlet extraction was performed using methanol, ethanol and n-hexane as the solvents. MCF-7 cells were treated with extracts at concentrations of 5 μg/mL, 50 μg/mL, 100 μg/mL, and 200 μg/mL in 96-well tissue culture plates for durations of 24, 48, and 72 hours. Cell viability was assessed using the CCK-8 assay at 450nm. The n-hexane extract at 50 μg/mL showed the highest inhibitory effect, reducing cell viability to (94.25 ± 0.08) %, (61.40 ± 0.04) %, and (67.75 ± 0.02) % at 24, 48, and 72 hours, respectively. Moreover, gas chromatography-mass spectrometry analysis identified phytochemical compounds, such as 2',6'- Dihydroxyacetophenone, bis(trimethylsilyl) ether, 2-Thiobarbituric acid, tris(tertbutyldimethylsilyl), and Benzoic acid, 2,5-bis(trimethylsilyl)-, trimethylsilyl ester, which could account for its anti-proliferative effects. Further research is needed to isolate and purify these bioactive compounds to better understand their therapeutic potential.